Vasculoprotective effects of ginger (Zingiber officinale Roscoe) and underlying molecular mechanisms. Issue 5 (16th February 2021) - Li, Chao; Li, Jie; Jiang, Feng; Tzvetkov, Nikolay T.; Horbanczuk, Jaroslaw O.; Li, Yunlun; Atanasov, Atanas G.; Wang, Dongdong
Abstract : Bioactive constituents of ginger are reviewed. Vascular protective effects of ginger and a variety of mechanisms are presented. Ginger and its components show vasculoprotective effects in clinical trials. Abstract : Ginger ( Zingiber officinale Roscoe) is a common and widely used spice. It is rich in various chemical constituents, including phenolic compounds, terpenes, polysaccharides, lipids, organic acids, and raw fibers. Herein, we reviewed its effects on the vascular system. Studies utilizing cell cultures or animal models showed that ginger constituents alleviate oxidative stress and inflammation, increase nitric oxide synthesis, suppress vascular smooth muscle cell proliferation, promote cholesterol efflux from macrophages, inhibit angiogenesis, block voltage-dependent Ca 2+ channels, and induce autophagy. In clinical trials, ginger was shown to have a favorable effect on serum lipids, inflammatory cytokines, blood pressure, and platelet aggregation. Taken together, these studies point to the potential benefits of ginger and its constituents in the treatment of hypertension, coronary artery disease, peripheral arterial diseases, and other vascular diseases.